Intramedullary nail fixation of non-traditional fractures: Clavicle, forearm, fibula. (June 2017) - Dehghan, Niloofar; Schemitsch, Emil H.
Abstract: Locked intramedullary fixation is a well-established technique for managing long-bone fractures. While intramedullary nail fixation of diaphyseal fractures in the femur, tibia, and humerus is well established, the same is not true for other fractures. Surgical fixations of clavicle, forearm and ankle are traditionally treated with plate and screw fixation. In some cases, fixation with an intramedullary device is possible, and may be advantageous. However, there is however a concern regarding a lack of rotational stability and fracture shortening. While new generation of locked intramedullary devices for fractures of clavicle, forearm and fibula are recently available, the outcomes are not as reliable as fixation with plates and screws. Further research in this area is warranted with high quality comparative studies, to investigate the outcomes and indication of these fractures treated with intramedullary nail devices compared to intramedullary nail fixation.